MAPPING OF STINGLESS BEE FAUNA IN NAGALAND - AVINASH CHAUHAN; HEMANT KUMAR SINGH (The Bioscan, 2021)
A comprehensive survey was conducted to know the diversity of stingless bee fauna in Nagaland. The stingless bee specimens were collected from different districts under Nagaland state of India. Total 1568 samples were collected from forests and nesting hives. A new species of stingless bee, Tetragonula gressitti Sakagami was recorded for the first time. During the studies a total of six different species from different districts were reported. These species were categorised district wise and altitude wise ranged from 100 m to 3230 m AMSL based on GPS coordinates and distribution pattern was also observed. According to the numbers of species recorded from each district a species distribution map was created using the species diversity data. Among all different districts, highest five different species were recorded from district Peren followed by 4 species from Mokokchung district and Mon and Kiphire district with 3 species. Kohima, Zunheboto, Tuensang, Noklak and Wokha districts were least diversified for stingless bee fauna with only 2 species recorded. This was the first attempt in the country to map the stingless bee diversity. These studies will provide a base for further stingless bee diversity explorations and rearing experiments in the country.